A Feasibility Study of Power Generation from Sewage Using a Hollowed Pico-Hydraulic Turbine. (December 2016) - Uchiyama, Tomomi; Honda, Satoshi; Okayama, Tomoko; Degawa, Tomohiro
Abstract: This study is concerned with the feasibility of power generation using a pico-hydraulic turbine from sewage flowing in pipes. First, the sewage flow rate at two connection points to the Toyogawa River-Basin Sewerage, Japan, was explored for over a year to elucidate the hydraulic energy potential of the sewage. Second, the performance of the pico-hydraulic turbine was investigated via laboratory experiments that supposed the turbine to be installed in the sewage pipe at the connection points. This study indicates that the connection points have hydraulic potential that can be used for power generation throughout the year. It also demonstrates that the pico-hydraulic turbine can be usefully employed for power generation from sewage flowing in the pipe at the connection points.